PENGETAHUAN IBU MENYUSUI TERHADAP PEMBERIAN KOLOSTRUM DI PUSKESMAS PASUNDAN - Artin Irma Wiherlina; Dwi Hendriani; Rivan Firdaus (MMJ (Mahakam Midwifery Journal), 2023)
Abstract Breastfeeding is the process of giving breast milk which is very beneficial for the growth and development of babies, especially the first yellowish breast milk (colostrum). Colostrum is the first milk that comes out and is yellowish, usually coming out on the first day to the seventh day. Colostrum contains immune substances to protect babies from infectious diseases, such as upper respiratory tract infections, diarrhea, and other infectious diseases. To determine the relationship between knowledge of breastfeeding mothers and the provision of colostrum in the work area of Pasundan Health Center Samarinda. This type of research is a type of quantitative descriptive research that uses a cross sectional design. The population is all breastfeeding mothers 0-3 months in the work area of Pasundan Health Center Samarinda. The sample is 38 respondents based on total sampling. Data collection uses primary and secondary data. Analysis technique with Sperman rank. The results of statistical research using the Spearman Rank test showed that p = 0.000 (p < 0.05). The Correlation Coefficient value obtained is 0.893 so that it can be said that the close relationship between the two variables is very strong and has a positive correlation direction. There is a relationship between knowledge of breastfeeding mothers on colostrum administration in the work area of Pasundan Health Center Samarinda. Keywords: Knowledge, Breastfeeding Mothers , Colostrum. Abstrak Menyusui adalah proses pemberian Air Susu Ibu yang sangat bermanfaat bagi pertumbuhan dan perkembangan bayi khususnya pemberian ASI pertama yang berwarna kekuningan (kolostrum). Kolostrum merupakan ASI yang pertama kali keluar dan berwarna kekuningan, biasanya keluar pada hari pertama sampai hari ketujuh. Kolostrum mengandung zat kekebalan tubuh untuk melindungi bayi dari penyakit infeksi, seperti infeksi saluran pernafasan atas, diare, dan penyakit infeksi lainnya. Mengetahui hubungan pengetahuan ibu menyusui terhadap pemberian kolostrum di Wilayah Kerja Puskesmas Pasundan Samarinda. Jenis penelitian ini merupakan jenis penelitian deskriptif kuantitatif yang menggunakan rancangan Cross Sectional. Populasi yaitu seluruh ibu menyusui 0-3 bulan di Wilayah Kerja Puskesmas Pasundan Samarinda. Sampel berjumlah 38 responden berdasarkan total sampling. Pengumpulan data menggunakan data primer dan sekunder. Tekhnik analisis dengan Sperman rank. Hasil penelitian statistik menggunakan uji Spearman Rank didapatkan bahwa p = 0.000 (p< 0,05). Diperoleh nilai Correlation Coefficient sebesar 0,893 sehingga dapat dikatakan keeratan hubungan antara kedua variabel tersebut ialah sangat kuat dan memiliki arah korelasi bernilai positif . Terdapat hubungan pengetahuan ibu menyusui terhadap pemberian kolostrum di Wilayah Kerja Puskesmas Pasundan Samarinda Kata kunci : Pengetahuan, Ibu Menyusui, Kolostrum